PENGARUH CARA EKSTRAKSI TERHADAP PEROLEHAN KADAR EKSTRAK, KADAR SENYAWA FENOLAT TOTAL DAN DAYA ANTIOKSIDAN DAUN DEWA (Gynura pseudochina (Lour). DC ) - Fita Selonni; Harrizul Rivai; B A Martinus (Jurnal Akademi Farmasi Prayoga, 2018)
Effect of extraction methods on recovery of phenolic compounds and antioxidant activity of Gynura pseudochina (Lour ). DC ). have been evaluated. The determination of phenolic compounds was carried out accourding to Folin Ciocalteu method and antioxidant activity was evaluated by DPPH method, calculated as gallic acid equivalent (GAE). The result of research indicate that acquirement of four way extract rate of extraction maceration, soxhletation, percolation, reflux as follow 16.54%, 12.01%, 8,20%, 15,04% and the determination of phenolic compound showed the result for maceration, soxhletation, percolation, reflux as follow 26.0095 mg/g, 23.6149 mg/g, 13.86515 mg/g, 10.6792 mg/g respectively. Their antioxidant activities were 1.892 µg/ml, 2.052 µg/ml, 2.607 µg/ml, 2.325 µg/ml, respectively. The result of research indicate of acquirement, the determination of phenolic compound and antioxidant activities of four way extract is maceration.